Vegetation Changes Viewed from Pollen Analysis in Rarotonga, Southern Cook Islands, Eastern Polynesia. Issue 2 (2014) - Fujiki, Toshiyuki; Okuno, Mitsuru; Moriwaki, Hiroshi; Nakamura, Toshio; Kawai, Kei; McCormack, Gerald; Cowan, George; Maoate, Paul T
Abstract : This study presents accelerator mass spectrometry (AMS) radiocarbon dates and pollen assemblages of 400-cm core sediments collected from the Karekare Swamp in Rarotonga, Southern Cook Islands, to investigate vegetation changes on the island, in particular those induced by human impacts. Eight 14 C dates of charcoal and higher plant fragment samples indicate that the sediments accumulated since ∼6.0 cal kBP, with an apparent interruption of deposition (hiatus) from 130 to 132 cm in depth, corresponding to ∼2.8 to 0.7 cal kBP. The appearance of Chenopodiaceae pollen from upland weeds, and Cucurbitaceae and Vigna pollen grains from cultivated plants suggest that human influence existed in core sediments above 130 cm in depth. The increased abundance of Pandanus pollen and monolate-type fern spores also implies the existence of human activity.